Nutrient content in tissues of Groenlandia densa, Myriophyllum spicatum and Zannichellia palustris: an attempt to understand the intercompartmental relationships in a small stream in the Middle Atlas Mountains of Morocco - Nouri Ayoub; Bihaoui Abdesslam; Hammada Soumaya; Chillasse Lahcen (Oceanological and Hydrobiological Studies)
Research has long focused on the relative importance of leaves and roots as sources of nutrient supply for macrophytes, as well as the function each stream compartment plays in their growth and development. This study aims to expand the debate on aquatic ecology and to better understand the connection between compartments in aquatic systems by highlighting the relationship observed in rivers between nutrients in macrophytes tissues, water, and sediments. We measured the concentrations of P-PO4, N-NO3 and N-NH4 in three different compartments of the Amengous stream in the Middle Atlas of Morocco. Myriophyllum spicatum (L.), Groenlandia densa (L.) Fourr. and Zannichellia palustris (L.) were selected as plant species. Our results show that even if the species coexist in the same habitat, they respond differently to nutrient richness. G. densa has a higher nutrient accumulation capacity than M. spicatum and Z. palustris and prefers the water compartment as a nutrient source. Although M. spicatum can accumulate phosphate compounds from water and sediment, ammonium is not its preferred nitrogen source. Z. palustris shows a tendency to accumulate nitrogen compounds through the roots, while it prefers the assimilation of phosphorus compounds through the leaves rather than the roots.